The effect of process monitoring on beyond‐the‐job process improvements - Schedlinsky, Ivo; Schmidt, Maximilian; Sommer, Friedrich; Wöhrmann, Arnt (Contemporary Accounting Research, 2025)
Abstract Although it has always been important for firms that employees innovate predefined processes, the working environment in which employees implement these processes has significantly changed. Currently, the working environment is often characterized by employee surveillance; that is, the way in which employees conduct a process is monitored. In the current study, we present the results of an experiment examining the effect of process monitoring on process improvements by employees. Although previous accounting literature has reported negative effects of monitoring techniques on several organizational outcomes, we show that process monitoring can have a positive effect on employees' implementation of process improvements in the absence, but not in the presence, of a firm's error avoidance policy. Without an error avoidance policy, employees are motivated to create a favorable impression in front of management by implementing process improvements. This finding has important implications for business practice. From a broader perspective, we show that the influence of action controls depends on the parameters of a cultural control.